Upgrade and repair with Jean Andrews - Andrews, Jean (Premier Press, 2003)
Covering hardware and operating systems, "Upgrade and Repair with Jean Andrews" is the most thorough, step-by- step book available for learning the fundamentals of supporting and troubleshooting computer hardware and operating systems. It covers new technologies in CPUs, motherboards, notebooks, printers, and PDAs, as well as Windows 2000, NT, 9x, DOS, Linux, and Mac. The hands-on format is designed to quickly take you from ?just-a-user? to ?I-can-fix-this!?